Design, synthesis, and biological evaluation of 2-(4-(methylsulfonyl) phenyl) indole derivatives with promising COX-2 inhibitory activity - Ahmed M. M. Shaker, Eman K. A. Abdelall, Khaled R. A. Abdellatif , , Hamdy M. Abdel-Rahman , (Journal of Applied Pharmaceutical Science, 2018)
A series of 2-(4-(methylsulfonyl)phenyl)-1-substituted-indole derivatives 4a–f was designed and synthesized as indomethacin analogs; All synthesized compounds were assessed for their in vitro COX-2 inhibition effect as well as in vivo anti-inflammatory activity using indomethacin as a reference drug. All synthesized compounds showed good anti-inflammatory activity and more selectivity for COX-2 inhibition. A molecular modeling study was carried out and the results were compatible with that derived from in vitro COX-2 inhibition assays.
Keywords: Indole, indomethacin, anti-inflammatory activity, selective COX-2, molecular modeling.